Pengembangan Perangkat Pembelajaran Matematika Berbasis RME di Sekolah Dasar - Kurnia Puspita Sari; Yerizon Yerizon; Yanti Fitria; Desyandri Desyandri (Universitas PGRI Madiun, 2021)
This study aims to describe a valid, practical and effective RME-based mathematics learning tool for increasing the ability to understand mathematical concepts of elementary school students. The research was conducted at SDN 41 Kinali, West Pasaman Regency. There were 27 grade students in grade IV as research subjects. This type of research is the development with the Plomp model. The validity level of the aspects of content, language, presentation by the validator is 90.09% with a very valid category. The practicality of the learning tools from the teacher's response was 97.3% and the response of students was 85.53% which means very practical. Then the average final test results of the students were 90.83. Thus it is known that the developed RME-based mathematics learning tool is suitable for use in grade IV SD.